Computing efficient solutions to fuzzy multiple objective linear programming problems - Li, Xue-quan; Zhang, Bo; Li, Hui (Fuzzy sets and systems, 2006)
In this paper, we improve the fuzzy compromise approach of Guu and Wu by automatically computing proper membership thresholds instead of choosing them. Indeed, in practice, choosing membership thresholds arbitrarily may result in an infeasible optimization problem. Although we can adjust minimum satisfaction degree to get fuzzy efficient solution, it sometimes makes the process of interaction more complicated. In order to overcome this drawback, a theoretically and practically more efficient two-phase max–min fuzzy compromise approach is proposed in this paper. Moreover, the efficiency of the two-phase approach is verified by an example.